Perception of patient safety culture among undergraduate dental students: a cross-sectional study - Jeetendar; Mariyam Iqbal; Mohid Abrar Lone; Maham Muneeb Lone; Maria Shakoor Abbasi; Naseer Ahmed; Muhammad Saad Shaikh (BMC Medical Education)
Abstract Objectives Although patient safety has received a lot of emphasis in medicine and nursing, data regarding patient safety perception in dentistry are limited, particularly among dental students. Given the increasing risk of safety hazards, curriculum developers need evidence to guide their implementation in undergraduate studies. This study aimed to determine patient safety culture among undergraduate dental students in Pakistan. Methods A cross-sectional analytical study was conducted among dental students (n = 281) of Sindh, Pakistan. The average positive response rate for each domain and frequency of each demographic variable were determined. The chi-square test was employed to compare the differences in perception between the various study groups. Statistical significance was set at p < 0.05. Results Based on the demographic variables, most of our respondents were female (60.5%), final year (59.1%), and public college students (53%). The study found that more than 50% of participants had a positive perception of safety in areas of teamwork, job satisfaction, work conditions, and management support. However, for stress recognition and safety climate, around 49% students had a positive response. Among the demographic variables, significantly larger number of females (56.4%, p = 0.014) and third year students (59.2%, p = 0.025) disagreed that it was difficult to speak up if they felt a problem with patient care, compared to males 43 (38.7%) and final year students 71 (42.8%). Conclusion Measuring patient safety culture in developing nations holds significant potential and can be implemented to inform safety initiatives. The data in our study show a significantly positive attitude towards safety culture among dental students. This study set the stage for more detailed research on patient safety culture in Pakistan.